QTL Underlying Reniform Nematode Resistance in Soybean Cultivar Hartwig (Atlas Journal of Biology, 2017)
Nematodes are one of the most destructive plant-parasitic pests in soybeans [Glycine max (L.) Merrill]. Among the nematodes, soybean cyst nematode (SCN, Heterodera glycines Ichinohe), southern root-knot nematode [RKN, Meloidogyne incognita (Kofoid and White) Chitwood], and reniform nematode (RN, Rotylenchlus reniformis Linford and Oliveria) are often the most problematic in soybean yield production. The plant introduction PI437654 has been used previously to map RN quantitative trait loci (QTL). However, ‘PI437654’ is non-domesticated. ‘Hartwig’ was the first domesticated cultivar to introgress some of the resistances from PI437654. The aims here were to map QTL underlying RN resistance in Hartwig. A cross between Flyer and Hartwig (n=92) was created to map QTL that underlie both SCN and RN resistance. The F × H population was phenotyped at the nematology lab at the University of Arkansas in 2014 and 2015 The F × H was genotyped with 140 polymorphic microsatellite markers (simple sequence repeats, SSR). In this study, 4 SSRs were highly significant (P< 0.001) associated by ANOVA and composite interval mapping and each were determined to identify a QTL. There were QTL on Chr. 12 (LG H, Satt353), and 3 on Chr. 18 (LG G, Satt275, Satt163, and Satt309). The beneficial alleles all derived from Hartwig. Satt353 has previously been reported to link to sudden death syndrome (SDS) QTL, and all three Satt markers on LG G have been reported to link to rhg1.Therefore, Hartwig and cultivars derived from it (‘Anand’, ‘Ina’) may be used to address the growing RN problems.